Analysis of the interaction of an industrial effluent with the Water Quality Index of the Pessegueirinho River, Curitibanos, Santa Catarina, Brazil - Campos, Roger Ferreira Francisco de; Borga, Tiago; Vazquez, Eric Marcos (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2017)
Water resources are losing their natural characteristics due to anthropic interaction, causing contamination of water sources and generally impairing environmental quality. In view of the above, this study aims to evaluate the water quality index of a water body that receives treated industrial effluent. The work was developed in the Rio Pessegueirinho located in the municipality of Curitibanos/SC, through parameters established by the Companhia de Tecnologia de Saneamento Ambiental - CETESB of the state of São Paulo, obtaining a poor to optimum index. The study site has a “Good” quality classification due to its variation between 51 and 79, however the interaction of the industrial effluent even though it was with the values of release according to the pertinent legislation presented a negative interaction, since the greater the anthropic interaction greater loss of water body quality. Thus, the present study aims at the importance of monitoring the WQI by the present company and other companies that release their effluents directly into water bodies.